Optimization of Arithmetical Operators for the Enhanced Wallace Stage - K. Gugan; S. V. Saravanan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In the field of Digital signal processing (DSP), the reduction of some logical elements counts is one of the main considerations. To minimize the area, computational delay, and power, the digital form FIR filter is to be implemented. The optimization of the ATP (Area, Time and Power) is achieved by using the efficient multiplication and accumulation unit (MAC). In this work, the direct form FIR filter with the efficient MAC unit is presented. At the initial stage, the half adders and full adders are to be modified by the reduction of the logical gates. The modified half and full adder are implemented in the Wallace tree multiplier for performing the efficient multiplication process. Carry save adder is divided into the two stages to reduce the computational delay of arithmetical operators. The proposed MAC design is implemented in the direct form FIR filter by using the HDL language.